Omani Mehri A New Grammar with Texts - Rubin, Aaron D. (Brill, 2018)
This book contains a comprehensive grammatical description of Mehri, an unwritten Semitic language spoken in the Dhofar region of Oman, along with a corpus of more than one hundred texts. Topics in phonology, all aspects of morphology, and a variety of syntactic features are covered. The texts, presented with extensive commentary, were collected by the late T.M. Johnstone. Some are published here for the first time, while the rest have been newly edited and translated, based on the original manuscripts. Semitists, linguists, and anyone interested in the folklore of southern Arabia will find much valuable data and analysis in this volume, which is the most detailed grammatical study of a Modern South Arabian language yet published.